Communicating green in Mekong Delta agritourism: greenwashing or green fantasy? - Hoang, Mi; Minh, Tan Le; Hoang, My Tran Le; Nguyen Khanh, Ngan (Frontiers in Communication, 2025)
Background contextThe Mekong Delta’s agritourism potential is growing through government initiatives and unique attractions, but rapid development raises sustainability concerns amid gaps between promotional narratives and actual tourist experiences. This study examines how “green” efforts are framed across government, business, and media channels, identifying disparities to improve sustainability communication and practices.Methods usedThis study collects agritourism communication data from four sources, including government websites, business promotions, media, and tourist reviews. A hybrid coding approach analyzed the data using 14 pre-defined themes. Data is qualitative and quantitative analysis with CDA, RTA and CL.Key findingsMedia coverage romanticizes agritourism, lacks critical voices and technological innovation, while government websites emphasize green policies and digital transformation but risk greenwashing with vague climate plans. Tourism companies promote “green” imagery but show clear greenwashing signs such as lack of certifications, low eco-infrastructure, whereas international tourists report mixed experiences, and domestic tourists note gaps between promoted ideals and actual infrastructure. Furthermore, a policy communication gap exists while government campaigns promote certifications like OCOP, but businesses ignore these in marketing, revealing a disconnect between public-sector sustainability efforts and private-sector implementation.ImplicationsThere is the disconnect between policy promotion and private-sector implementation in the Mekong Delta’s agritourism, risking duplicated efforts and greenwashing. Future research should expand stakeholder interviews, include local media, and compare ASEAN agritourism markets to assess if similar sustainability communication gaps persist regionally.